Poverty Alleviation Strategies Through Sharia Microfinance Institutions Politico-Economics Study With Tawhidi Approach - Heriyanto, Raden; Mariyanti, Tatik (Pandawan, 2022)
This research aims to formulate a poverty alleviation strategy in Indonesia by empowering Islamic Microfinance Institutions (IMFI) based on political-economic studies. The Indonesian political-economic system is stipulated in Article 33 of the 1945 Constitution and its Explanatory Paragraph, making the people the center of attention for national economic development. The research uses the Analytic Network Process (ANP) method developed by Saaty. The ANP construction uses a model consisting of 3 main clusters, namely Problems, Solutions, and Strategies. The qualitative-quantitative assessment data is determined based on the Saaty Scale obtained through an in-depth interview of 9 expert respondents and practitioners in Islamic economics and finance. The results show that poverty alleviation strategies need to be carried out through cultural and structural approaches. The cultural approach includes revitalizing the concept of the people's economy as stated in the 1945 Constitution, campaigning for using the domestic product, socialization to increase literacy about waqf and zakat, improving the practices of bureaucratic ethics, and strengthening the values of togetherness and anti-monopoly. The strategy at structural approach is carried out by implementing policies to enhance the role of cooperatives in the national economy; increasing the education budget for the poor and needy; increased coordination between authorities; bureaucratic reform; and honest and fair law enforcement against corruption. For the micro-level at the LKMS institution, the cultural approach is carried out by strengthening literacy on Islamic financial instruments, increasing financial inclusion programs, social inclusion programs, and strengthening methods for obtaining funding sources from Islamic financial instruments. On the structural side, it is necessary to improve the professionalism and capability of supporting LKMS, institutional strengthening, internal control and supervision system, improvement of supporting infrastructure, and enhancing service convenience.